Coping with Cognitive Impairment in People with Parkinson's Disease and Their Carers: A Qualitative Study. (8th April 2018) - Lawson, Rachael A.; Collerton, Daniel; Taylor, John-Paul; Burn, David J.; Brittain, Katie R.
Abstract : Cognitive impairment is common in Parkinson's disease (PD). However, the psychosocial impact of living and coping with PD and cognitive impairment in people with PD and their carers have not been explored. This paper draws on a qualitative study that explores the subjective impact of cognitive impairment on people with PD and their carers. Thirty-six one-to-one interviews were completed; people with PD were from three groups: normal cognition, mild cognitive impairment, and dementia. Data collection and analysis were iterative, and verbatim transcripts were analysed using thematic analysis. Themes were interpreted in consultation with coping and adaptation theory. The analysis revealed four main themes: threats to identity and role, predeath grief and feelings of loss in carers, success and challenges to coping in people with PD, and problem-focused coping and finding meaning in caring. Our data highlight how cognitive impairment can threaten an individual's self-perception; the ostensible effects of cognitive impairment depended on the impact individual's perceived cognitive impairment had on their daily lives. For carers, cognitive impairment had a greater emotional impact than the physical symptoms of PD. The discussion that developed around protective factors provides possible opportunities for future interventions, such as psychological therapies to improve successful adjustment.